The Role of Influencers in Mediating the Effects of Online Reviews, Promotional Content, and Price on Consumer Trust and Purchase Decisions: Evidence from TikTok Shop Chimore Indonesia - Diana Yuliani (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
The rapid growth of social commerce has transformed consumer purchasing behavior, particularly through platforms such as TikTok Shop. Online reviews, promotional content, competitive pricing, and influencer marketing play essential roles in shaping consumer trust and purchase decisions. Competitive pricing, and influencer marketing, play essential roles in shaping consumer trust and purchase decisions. This study aims to analyze the influence of online reviews, promotional content, and price on consumer trust and purchase decisions, while also examining the mediating role of influencers in these relationships. The research adopts a quantitative approach using a survey method. Data are collected through questionnaires distributed to Generation Z consumers residing in Ungaran who have previously purchased products from Chimore Indonesia through TikTok Shop. The sampling technique applies purposive sampling, while data analysis is conducted using Structural Equation Modeling (SEM) with SmartPLS. The proposed conceptual framework is expected to explain how influencers strengthen consumer confidence in online shopping environments and encourage purchasing decisions. The findings of this study are expected to provide practical implications for business practitioners in designing effective digital marketing strategies and contribute to the development of consumer behavior literature within social commerce platforms.